Gradiente de recuperación longitudinal en la estructura de la ictiofauna en un río andino regulado (2014)
Changes in the biota inhabiting the streams downstream of dams have been the subject of numerous studies but few have focused on recovery gradients downstream of the dam or the influence of seasonality on the pulse of the flow in regulated streams. Since 2000 the hydro-power company Isagen SA E.S.P. has been monitoring some emerging characteristics of the fish community in the lower basin of La Miel River (Magdalena River Basin) downstream of the dam to document the response of the fish fauna to new environmental conditions. Based on this monitoring, we tested the hypothesis that there would be a gradient of recovery in the fish assemblage characteristics along the longitudinal axis, downstream from the turbine’s output to its mouth in the Magdalena River. The highest values observed in the dominance index were a result of the arrival of migratory species to the site of the water discharge from the dam during low water period. Finally there is a need to weigh alternative locations of a dam taking into consideration the possibility that downstream tributaries can diminish the impact of the dam and hydropower plant operation.